2006
DOI: 10.1098/rstb.2006.1906
|View full text |Cite
|
Sign up to set email alerts
|

Early anaerobic metabolisms

Abstract: Before the advent of oxygenic photosynthesis, the biosphere was driven by anaerobic metabolisms. We catalogue and quantify the source strengths of the most probable electron donors and electron acceptors that would have been available to fuel early-Earth ecosystems. The most active ecosystems were probably driven by the cycling of H 2 and Fe 2C through primary production conducted by anoxygenic phototrophs. Interesting and dynamic ecosystems would have also been driven by the microbial cycling of sulphur and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
311
2
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(347 citation statements)
references
References 90 publications
(173 reference statements)
11
311
2
8
Order By: Relevance
“…Previous studies have reported a growth advantage from NDFO by Acidovorax species in both batch and continuous-flow cultures (12,14), in addition to the accumulation of nitrite (NO 2 Ϫ ) and periplasmic mineral encrustations (26). On the basis of our findings with A. ebreus, we postulate that all nitrate-respiring organisms are innately capable of catalyzing NDFO, but the survival and growth benefits obtained are dependent on the ability to overcome Fe(II), NO 2 Ϫ , and NO toxicity. Our findings have implications for understanding the evolution of Fe(II) oxidation as a microbial metabolism, the impact of Fe(II) on nitrate-reducing communities, and the influence of Fe(II) on the product distribution of microbial nitrate reduction.…”
mentioning
confidence: 46%
See 3 more Smart Citations
“…Previous studies have reported a growth advantage from NDFO by Acidovorax species in both batch and continuous-flow cultures (12,14), in addition to the accumulation of nitrite (NO 2 Ϫ ) and periplasmic mineral encrustations (26). On the basis of our findings with A. ebreus, we postulate that all nitrate-respiring organisms are innately capable of catalyzing NDFO, but the survival and growth benefits obtained are dependent on the ability to overcome Fe(II), NO 2 Ϫ , and NO toxicity. Our findings have implications for understanding the evolution of Fe(II) oxidation as a microbial metabolism, the impact of Fe(II) on nitrate-reducing communities, and the influence of Fe(II) on the product distribution of microbial nitrate reduction.…”
mentioning
confidence: 46%
“…3c). These results suggest that Nar directly catalyzes NO 3 Ϫ reduction coupled to Fe(II) oxidation (54) and/or NO 2 Ϫ is produced to further react with Fe(II) through the abiotic and biotic mechanisms previously discussed.…”
Section: Evidence Against An Inducible Fe(ii) Oxidoreductase Inmentioning
confidence: 84%
See 2 more Smart Citations
“…Sufficiently high concentrations of H 2 occur in the vent fluids of these systems to sustain an ecosystem based on H 2 -driven chemolithoautotrophic primary producers such as methanogens. Moreover, an H 2 -driven ecosystem is the most probable candidate habitat for the earliest life on Earth (Russell and Hall 1997;Sleep et al 2004;Kelley et al 2005;Takai et al 2006;Canfield et al 2006). On this basis, it has been hypothesized that hydrothermal fluids with H 2 , sufficiently abundant to sustain methanogens, existed in the early Earth (Takai et al 2006).…”
Section: 3mentioning
confidence: 99%